A new approach to analyze the dynamic strength of eggs - Trnka, Jan; Nedomová, Šárka; Kumbár, Vojtěch; Šustr, Michal; Buchar, Jaroslav (Journal of biological physics, 2016)
The mechanical behavior of eggshell was determined in terms of average rupture force and corresponding deformation. For the experiment, we selected goose eggs (Anser anser f. domestica). Samples of eggs were compressed along their x-axis and z-axis. The effect of the loading orientation can be described in terms of the eggshell contour curvature. Two different experimental methods were used: compression between two plates (loading rates up to 5 mm/s) and the Hopkinson split pressure bar technique. This second method enables achieving loading rates up to about 17 m/s. The response of goose eggs to this high loading rate was characterized also by simultaneous measurement of the eggshell surface displacements using a laser vibrometer and by the measurement of both circumferential and meridian strains.
Keywords: mechanický stres; mechanické jevy; ovum; Ovum; Stress, Mechanical; Geese; pevnost v tlaku; zvířata; tlak; Pressure; testování materiálů; Compressive Strength; Materials Testing; Mechanical Phenomena; husy; Animals